Long-term surgical outcome and risk factors in living kidney donors - Sterkenburg, Anthe; Kulu, Yakup; Mieth, Markus; Sommerer, Claudia; Zeier, Martin; Mehrabi, Arianeb; Büchler, Markus W.; Hoffmann, Katrin (Transplantation proceedings, 2020)
Context - Studies on the surgical outcome in living kidney donors mainly report perioperative complications with short follow-up. - Objective - The objectives of this study are to evaluate the long-term surgical outcome in living kidney donors and to identify donors with an increased risk for a complicated postoperative course. - Basic Procedures - A prospectively collected database of 496 living kidney donors at the Department of General, Visceral, and Transplantation Surgery of the Ruprecht Karls University Heidelberg was retrospectively analyzed in a retrospective, observational single-center study. - Results - The median follow-up time was 37 months. The perioperative severe complication (Clavien-Dindo IIIb) rate was 2.8%, the early postoperative (PO) severe complication rate (1-3 months post operation) was 0.7%, and the late PO severe complication rate (> 3 months post operation) was 8.4%. In multivariate analyses, male sex was associated with higher overall perioperative complication rate (odds ratio [OR], 1.930; P = .005) as well as higher rate of late PO complications (OR, 2.243; P = .014). An increased body mass index was associated with a higher late and severe (Clavien-Dindo ≥ IIIb) PO complication rate (OR, 1.107; P = .009 and OR, 1.105; P = .008, respectively). - Conclusions and Relevance - Long-term surgery-associated severe complications occur in 8.4% of kidney donors. Older age is associated with an increased operative time, greater intraoperative blood loss, and longer PO hospital stay. Male donors and donors with an increased body mass index have a higher risk for a complicated PO course after kidney donation. Within a shared decision-making process before living kidney donation, special awareness should be brought to these facts.
Gesehen am 27.04.2020